2015
DOI: 10.1007/s11552-015-9779-2
|View full text |Cite
|
Sign up to set email alerts
|

Scapholunate Instability after Distal Radius Volar Plating

Abstract: Background Prior to volar locked plating and early motion protocols, ligamentous injuries incidentally associated with distal radius fractures may have been indirectly treated with immobilization. Our goal was to determine the prevalence of scapholunate instability in our population, while identifying those who may have had progression of instability. Methods We retrospectively reviewed 221 distal radius fractures treated with a volar locking plate during a 6-year period. Average patient age was 59 years. Stan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 25 publications
0
8
0
3
Order By: Relevance
“…In the acute posttraumatic radiographs of distal radius fractures, a scapholunate diastasis (>3mm) is often seen [ 8 , 16 , 17 ]. However, these are not always clinically relevant.…”
Section: Introductionmentioning
confidence: 99%
“…In the acute posttraumatic radiographs of distal radius fractures, a scapholunate diastasis (>3mm) is often seen [ 8 , 16 , 17 ]. However, these are not always clinically relevant.…”
Section: Introductionmentioning
confidence: 99%
“…More recent studies indicate that surgical repair of SLI is especially worthwhile in patients with (radiographic) signs of severe SLI and/or a high functional demand of their injured wrist. 2,29 Overall, our findings indicate that the current abilities to radiographically diagnose SLI effectively in the setting of a DRF are suboptimal. Based on our data, it appears that radiographic diagnosis of SLI is challenging and often does not seem to correspond with clinical concerns by the treating surgeons.…”
Section: Discussionmentioning
confidence: 86%
“…Numerous studies have reported varying incidences of SLI associated with DRFs, based on either medical imaging or arthroscopy of the wrist. [1][2][3][4][5][14][15][16] The incidence of specifically radiographically diagnosed SLI in patients who were operatively treated for DRFs seems to lie between 8.1 and 32%. 2,15 Although radiographs are considered to be a reliable tool in diagnosing SLI, 17,18 plain radiographs seem to be more useful for excluding rather than confirming SLI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A pesar de esto, no existen investigaciones que a largo plazo nos permitan identificar cuáles son sintomáticas y deben ser tratadas en este contexto. 30 Es frecuente observar en radiografías de fracturas de radio distal distasis del espacio escafosemilunar mayor de 3 mm; 31,32,33 sin embargo, no siempre es clínicamente relevante, tal vez debido a la cicatrización ligamentaria durante la inmovilización. 34,35,36,37 La artroscopía se ha convertido en una herramienta de uso frecuente para diagnóstico y tratamiento de patología de muñeca entre los cirujanos de miembro superior, es importante destacar que la curva de aprendizaje es exigente.…”
Section: Inclinación Radialunclassified